Botulinum Toxin's Effects on Muscle Tone and Joint Mobility in Children with Congenital Zika Syndrome – A Case Series - Silva, Patrícia Juliana da; Brito, Ana Stela Salvino de; Silva, Mariana Balbino da; Barros, Nathalia Nogueira Romariz; Tavares, Jousilene Sales; Gama, Gabriela Lopes (Revista Brasileira de Ortopedia, 2024)
Objective To evaluate the effects of the botulinum toxin (BTX-A) on muscle tone and joint mobility in children with congenital Zika syndrome (CZS).Methods This was a longitudinal case series carried out in a Support Center for Children with Microcephaly, located in Northeastern Brazil. We collected data from the institution's medical records, containing information about muscle tone and passive joint mobility measured at least 3 months before and 4 weeks after BTX-A application.Results We evaluated 13 children (9 boys) with a mean age of 77 ± 7.1 months. After BTX-A application, a bilateral reduction in the hypertonia level was observed in the elbow flexor (p < 0.01) and hip abductor (p < 0.05) muscles.Conclusion No changes were observed in joint mobility and no adverse effects were reported by caregivers after application. The use of BTX-A can reduce hypertonia in CZS children, with no impact on joint mobility.
Keywords: arthrometry articular; muscle hypertonia; muscle spasticity; Zika virus infection